EVALUASI PENYALURAN BANTUAN BAGI PELAKU USAHA MIKRO DI DESA POTANGA KECAMATAN BOLIYOHUTO KABUPATEN GORONTALO - Pakudu, Robin; Djafar, Franky; Tuna, Nurain (Jurnal Administrasi Negara dan Ilmu Pemerintahan, 2024)
This research aims to find out and evaluate how aid is distributed to micro businessman (BPUM) in Potanga Village, Boliyohuto District, Gorontalo Regency. The method uses a qualitative approach with descriptive research type. The results showed, it can be concluded the distribution of aid for micro businessman (BPUM) in Potanga Village has not gone well. From the 5 (five) indicators related to policy evaluation, it has not gone well. In terms of effectiveness indicators, it was found the distribution was less effective because it was distributed to several people who did not even have businesses and was only used for household consumption needs. Beside that, even though it was distributed to MSMEs, in reality it did not meet needs. In the Sufficiency indicator, it was found the community was helped by this program because it had helped in providing capital for small and medium businesses in the village. In terms of equity indicators, it is found not all people who own businesses receive this assistance due to the criteria set by the government which are often difficult to fulfill, thus this is one thing that causes not all people to receive this assistance. In the Responsiveness indicator, it is found the village government, in carrying out its main duties, has tried as much as possible to help the community in fulfilling the criteria set by the government, but the government has no right to determine the program's acceptance. In the accuracy indicator, it was found that program distribution was not in accordance with the established criteria.